Application of the Gagnon and Collay Model in Improving High School Students' Learning Outcomes in Biology Subjects - Anci Mariesi; Maryam Zand Vakili; Khder Niazi Nooraldeen Chalabi (Indonesian Journal of Education Research (IJoER), 2024)
Purpose of the study: This research aims to investigate the effectiveness of applying the Gagnon and Collay Model in improving Biology learning outcomes for class XI students at Public Senior High School 1 Bone-Bone, North Luwu Regency. Methodology: This research is classroom action research which involves four components in each cycle. The research subjects consisted of 32 students of class XI Science 1 at Public Senior High School 1 Bone-Bone, North Luwu Regency. Data collection is carried out through tests and observation sheets in each cycle. Data analysis methods include qualitative and quantitative descriptive techniques. Main Findings: From the analysis of student learning outcomes tests in each cycle, it can be observed that the abilities of class XI Science 1 students at Public Senior High School 1 Bone-Bone, North Luwu Regency, have increased. After implementing the Gagnon and Collay Learning Model, the students' average score increased from 63.5 in cycle I to 90.38 in cycle II. This shows an increase in biology learning outcomes after implementing the Gagnon and Collay Learning Model. Novelty/Originality of this study: This research makes a significant contribution to the educational context by exploring and applying the Gagnon and Collay Model in improving student learning outcomes in Biology subjects. Through this approach, this research seeks to provide innovation in Biology teaching methods, aiming to create a learning environment that is more interactive, creative, and appropriate to the development of class XI Science 1 students.